Clinical Features Associated With Need for Mechanical Ventilation in Children With Guillain-Barré Syndrome: Retrospective Cohort From India. Issue 5 (28th February 2022) - Randhawa, Manjinder Singh; Iyer, Rajalakshmi; Bansal, Arun; Mukund, Bal; Angurana, Suresh Kumar; Nallasamy, Karthi; Jayashree, Muralidharan; Singhi, Sunit C.; Singhi, Pratibha; Baranwal, Arun Kumar; Sankhyan, Naveen
Abstract : OBJECTIVES: To analyze the clinical features associated with the need for mechanical ventilation (MV) in children with Guillain-Barré syndrome (GBS). DESIGN: Retrospective cohort study, 2010–2019. SETTING: PICU. PATIENTS: All children, 1 month to 12 years old, diagnosed with GBS in our single-center PICU. Intervention: Retrospective chart and data review. MEASUREMENTS AND MAIN RESULTS: Out of 189 children identified with a diagnosis of GBS, 130 were boys (69%). The median (interquartile range [IQR]) age was 6 years (3–9 yr). At admission, the Hughes disability score was 5 (4–5), and cranial nerve palsies were present in 81 children (42%). Autonomic instability subsequently occurred in a total of 97 children (51%). In the 159 children with nerve conduction studies, the axonal variant of GBS (102/159; 64%) predominated, followed by the demyelinating variant (38/189; 24%). All children received IV immunoglobulins as first-line therapy at the time of admission. The median (IQR) length of PICU stay was 12 days (3–30.5 d). Ninety-nine children (52%) underwent invasive MV, and median duration of MV was 25 days (19–37 d). At admission, upper limb power less than or equal to 3 ( p = 0.037; odds ratio (OR), 3.5 [1.1–11.5]), lower limb power less than or equal to 2 ( p = 0.008; OR, 3.5 [1.4–8.9]), and cranial nerve palsy ( p = 0.001; OR, 3.2 [1.6–6.1]) were associated with subsequent need for MV. Prolonged (> 21 d) MV was associated with more severe examination findings at admission: upper limb power less than or equal to 2 ( p < 0.0001; OR, 4.2 [2.5–6.9]) and lower limb power less than or equal to 1 ( p < 0.0001; OR, 4.5 [2.6–7.9]). CONCLUSIONS: In children with GBS, referred to our center in North India, severe neuromuscular weakness at admission was associated with the need for MV. Furthermore, greater severity of this examination was associated with need for prolonged (> 21 d) MV. Identification of these signs may help in prioritizing critical care needs and early PICU transfer.